Imaginária retabular colonial em São Paulo: estudos iconográficos - Passos, Maria José Spiteri Tavolaro [UNESP] (2015)
everal artistic languages flourished during the Brazilian colonial period and, among them, numerous samples reminiscent from the traditional sculpting technique applied to the construction of religious images may still be found. Designed for religious or civil spaces, the tridimensional production of sculpture character ranges from the elaboration of ornamental elements to the making of figures of saints (sacred images). Imbued by the rigid principles of the Counter-Reformation, the cult of saints became a powerful instrument of evangelization and catechesis, being disseminated after the 16th century by the activity of the religious orders in Brazil, which widely favored the popularization of the cult images, initially imported from Portugal and later produced in the very colony as well. These images would occupy the thrones in the niches of altarpieces in churches, chapels, household oratories and, on festivities, would gain the streets in processions. It is important to emphasize how fundamental the contribution of the third orders and brotherhoods were to disseminate and consolidate this vast work developed among local communities. From the 19th century on, changes in Brazilian politics, economy and society favored the entrance of new esthetic standards coming from Europe. This fact lead many churches to opt for reforms, including the replacement of pieces in clay or wood for new ones executed in series, which resulted in the loss of several ancient originals. However, even though frequently disregarded by studies, a significant number of works executed according to the traditional techniques is still maintained in catholic temples across the state of São Paulo, both in the capital and the interior or the coast. Through the inventory of a representative part of this collection, this work studied the religious imagery reminiscent of the colonial period, with emphasis in the erudite production for ...